Worsening spasticity due to catheter breakage during intrathecal baclofen therapy: a case report - Yasutaka Takagi; Hiroshi Yamada; Hidehumi Ebara; Hiroyuki Hayashi; Hiroyuki Inatani; Yuta Nakamura; Ryo Sugihara; Aki Nakanami; Kenji Kagechika; Tetsutaro Yahata; Satoru Demura (Journal of Medical Case Reports)
Abstract Background Intrathecal baclofen therapy can substantially improve symptoms in patients with severe spasticity owing to traumatic spinal cord injury, multiple sclerosis, cerebral paresis, or tethered cord syndrome. Problems associated with intrathecal catheters include migration, laceration, occlusion, or disconnection. Several case reports have described the management of catheter fragments. To the best of our knowledge, this is the first detailed report of the insertion of a new catheter. Case presentation A 64-year-old Japanese man with spinal myoclonus was undergoing intrathecal baclofen therapy; his spasticity was well controlled with intrathecal baclofen therapy but worsened 13 years after pump implantation. Imaging revealed spinal catheter breakage, and the catheter was retained in the spinal canal. We inserted a new catheter through a different intervertebral space without removing the original catheter. Postoperatively, the spasticity remained well controlled with intrathecal baclofen therapy. Conclusion This is the first detailed report on the insertion of a new catheter for intrathecal baclofen therapy at a different intervertebral space from the catheter breakage, without removal of the old intrathecal catheter.